1998
DOI: 10.1542/peds.102.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Rhinovirus, Respiratory Syncytial Virus, and Coronavirus Infections in Acute Otitis Media by Reverse Transcriptase Polymerase Chain Reaction

Abstract: These findings highlight the importance of common respiratory viruses, particularly HRV and RSV, in predisposing to and causing AOM in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
153
0
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(165 citation statements)
references
References 21 publications
3
153
0
9
Order By: Relevance
“…107 1952-1981 and 1985-1992, the mean percentage of cases with bacterial pathogens isolated from the middle ear fluids was 69% and 72%, respectively. 118 A large series from the University of Pittsburgh Otitis Media Study Group reported bacterial pathogens in 84% of the middle ear fluids from 2807 cases of AOM.…”
Section: Microbiologymentioning
confidence: 94%
“…107 1952-1981 and 1985-1992, the mean percentage of cases with bacterial pathogens isolated from the middle ear fluids was 69% and 72%, respectively. 118 A large series from the University of Pittsburgh Otitis Media Study Group reported bacterial pathogens in 84% of the middle ear fluids from 2807 cases of AOM.…”
Section: Microbiologymentioning
confidence: 94%
“…10,11 Total RNA was extracted from 250 L of sample with TriReagent LS (MRC, Inc, Cincinnati, OH) according to the manufacturer's protocol. The resulting RNA was dissolved in 30 L of diethylpyrocarbonate-treated water (Ambion Inc., Austin, TX) and stored at Ϫ80°C.…”
Section: Coronavirus Reverse Transcription-pcrmentioning
confidence: 99%
“…A 2-L aliquot of the RNA was tested in duplicate in a single-tube nested RT-PCR assay using the EZrTth RNA-PCR enzyme in a 50-L total volume (Applied Biosystems, Foster City, CA) with second-round inner primers (5 L) suspended in a hanging droplet in the lid. 11 The assay was performed by using HCoV OC43 outer primers O1 (5Ј-CCCAAGCAAACTGCTAC-CTCTCAG-3Ј) and O3 (5Ј-GTAGACTCCGTCAATATCGGTGCC-3Ј) and inner primers O1.1 (5Ј-CATCAGGAGGGAATGTTG-TACC-3Ј) and O3.1 (5Ј-TACTGGTCTTTAGCATGCGGTC-3Ј) in 25 mM Mn 2ϩ . 10 For HCoV 229E, the assay was performed by using outer primers E3 (5Ј-GGTACTCCTAAGCCTTCTCG-3Ј) and E5 (5Ј-GACTATCAAACAGCATAGCAGC-3Ј) 12 and inner primers E7 (5Ј-TCTGCCAAGAGTCTTGCTCG-3Ј) and E9 (5Ј-AGCAT-AGCAGCTGTTGACGG-3Ј) 1 with reduced (20 mM) Mn 2ϩ concentration.…”
Section: Coronavirus Reverse Transcription-pcrmentioning
confidence: 99%
“…Because pneumococcus is the most common bacterial cause of otitis media (OM), research over the past decade has focused on pneumococcal vaccination. [18][19][20][21][22] Pneumococcal conjugate vaccination in infancy has been shown to be (highly) effective in preventing invasive disease. [23][24][25] Regarding AOM, the clinical efficacy seems modest (6 -7%).…”
mentioning
confidence: 99%